Advanced practice nursing in Latin America and the Caribbean: regulation, education and practice - Keri Elizabeth Zug; Silvia Helena De Bortoli Cassiani; Joyce Pulcini; Alessandra Bassalobre Garcia; Francisca Aguirre-Boza; Jeongyoung Park
Abstract Objective: to identify the current state of advanced practice nursing regulation, education and practice in Latin America and the Caribbean and the perception of nursing leaders in the region toward an advanced practice nursing role in primary health care to support Universal Access to Health and Universal Health Coverage initiatives. Method: a descriptive cross-sectional design utilizing a web-based survey of 173 nursing leaders about their perceptions of the state of nursing practice and potential development of advanced practice nursing in their countries, including definition, work environment, regulation, education, nursing practice, nursing culture, and perceived receptiveness to an expanded role in primary health care. Result: the participants were largely familiar with the advanced practice nursing role, but most were unaware of or reported no current existing legislation for the advanced practice nursing role in their countries. Participants reported the need for increased faculty preparation and promotion of curricula reforms to emphasize primary health care programs to train advanced practice nurses. The vast majority of participants believed their countries' populations could benefit from an advanced practice nursing role in primary health care. Conclusion: strong legislative support and a solid educational framework are critical to the successful development of advanced practice nursing programs and practitioners to support Universal Access to Health and Universal Health Coverage initiatives.